Bowel vaginoplasty: a systematic review. Issue 5 (3rd September 2018) - Georgas, Konstantinos; Belgrano, Valerio; Andreasson, My; Elander, Anna; Selvaggi, Gennaro
Abstract: Among surgical procedures for constructing a neovagina, positive outcomes are reported in literature for bowel vaginoplasty for male-to-female transgenders and patients with vaginal aplasia. This systematic review shows outcomes of bowel vaginoplasty procedures, and rates the quality of evidence of the included studies. A search of the literature was performed in PubMed, Medline, Cochrane Library and SveMed+, in accordance with the PRISMA statement, between January 2016 and February 2018. The PICOS (patients, intervention, comparator, outcomes and study design) approach was used as inclusion criteria. Among 251 analyzed studies only 34 met inclusion criteria. Quality of evidence and methodology were rated according to GRADE and MINORS, respectively. Data from the included studies were extracted based on study characteristics, participants? specifics, type of intervention/treatment and type of outcome measures into data extraction forms. All studies were non-randomized with a high risk of bias and very low quality of evidence according to GRADE. Vaginal reconstruction with isolated bowel segments provides a self-lubricating neovagina with low rates of failure and revision, and without routine dilatation need. Furthermore, the use of laparoscopic techniques offers a better postoperative cosmetic appearance of the abdomen and a shorter hospital stay. Vaginoplasty using bowel segment is a safe and effective procedure that obtains excellent long-term results as reported by the included studies. Despite that further researches are needed improving methodology with larger populations, retrospective qualitative studies and report of outcome measurements using standardized evaluation tools as the Female Sexual Function Index.